On the dynamics of the Bianchi IX system - Buzzi, Claudio A.; Llibre, Jaume; da Silva, Paulo R. (Iop Publishing Ltd, 2007)
In this paper, we study the flow on three invariant sets of dimension five for the classical Bianchi IX system. In these invariant sets, using the Darboux theory of integrability, we prove the non-existence of periodic solutions and we study their dynamics. Moreover, we find three invariant sets of dimension four where the flow is integrable.